Czeskie »onkání« i »onikání«. Niedokończony artykuł ... - Orłoś, Teresa Z.; Bura, Renata (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2014)
Professor Teresa Zofia Orłoś‘s unfinished article has become a stimulus to write this paper on polite forms in the Czech language. The polite forms onkání and onikání were mainly used in Czech in the 18th century. During the Czech Revival they were not included in the literary norm (the 2nd person pl., i.e. vykání is used), however, in everyday communication they have appeared for a long period of time. Today onikání is used as an element expressing irony or parody. In literature it is used as a means of stylization of heroes’ description, particularly characterizing „simple” people or Jews (e.g. in Jewish anecdotes). The lack of onkání and onikání in contemporary Czech shows that the norm of polite forms undergoes changes. It is not given for good.
Keywords: Czech; polite forms; language etiquette; onkání; onikání